Family-Based Health Promotion for Child Stunting Prevention: Qualitative - Sri Wahyuni; Sarifudin Andi Latif; Farida Latif (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Stunting remains a significant global and national public health issue, including in Jeneponto Regency with a high prevalence. This problem is not only biological but also influenced by social, economic, and family behavioral factors, requiring family- and community-based health promotion approaches. This study employed a qualitative approach with a descriptive exploratory case study design. Informants were selected purposively until data saturation was reached, consisting of mothers with children under five (A1-A10), posyandu cadres (A11-A15), and health workers (A16-A25). Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically using NVivo. Four main themes were identified: family health literacy, parenting practices, community roles, and structural factors. The findings reveal a gap between knowledge and practice, low nutritional literacy, reliance on traditional information, and limited access to nutritious food and health services. The results indicate that stunting prevention behavior is shaped by the interaction of cognitive, social, and structural factors. The role of cadres as change agents is significant but not yet optimal due to limited capacity and program sustainability. Health promotion strategies are not yet optimal. Integrative, participatory, and context-sensitive family- and community-based approaches are needed to improve the effectiveness of stunting prevention.